Exploring the effects of subsidiary interdependence on the performance of global product launches. (3rd June 2019) - Mohr, Alexander; Unen, Marc Van; Fastoso, Fernando; Tihanyi, Can
We explore the effects of subsidiary interdependence on global product launch performance using a case-study design combining quantitative and qualitative data collected from subsidiaries participating in the global launch of a new drug by a major pharmaceutical multinational enterprise. The study combines pre-launch survey data on subsidiary interdependence with post-launch quantitative performance data to select eight of 67 subsidiaries involved in a global product launch. We also analyse information gathered through in-depth interviews with 19 subsidiary managers to explore various facets of the relationship with their headquarters and other subsidiaries. Our findings suggest that the positive effect of interdependence on global product launch success varies with subsidiaries' involvement in decision-making, with the division of labour and responsibilities, and with the existence of cognitive, relational and structural social capital. Based on our findings, we present several propositions regarding the effects of subsidiary interdependence on the success of global product launches.